DEVELOPMENT OF DISCOVERY LEARNING-BASED STUDENT WORKSHEETS (LKPD) TO IMPROVE STUDENTS' ANALYTICAL SKILLS IN AL-QUR'AN HADITH SUBJECT ON THE TOPIC OF INFAK AND SADAQAH IN CLASS VIII-A AT MTsN 1 RANTAUPRAPAT - Fikri Ramadhan Tambak; Dedi Masri (SOSIOEDUKASI, 2026)
This study aims to develop Discovery learning-based Student Worksheets (LKPD) on the topic of "Infak and Sadaqah" in the Al-Qur'an and Hadith course for eighth-grade students in Class VIII-A at MTsN 1 Rantauprapat to enhance their analytical skills. The study employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate) developed by Thiagarajan et al. (1974). Data were collected through expert validation sheets, teacher and student response questionnaires, and Higher-Order Thinking Skills (HOTS)-based test instruments consisting of essay questions administered as pretests and posttests. The results indicate that the developed worksheets achieved an average validity percentage of 93.12% (Highly Valid), an average practicality percentage of 96.41% (Highly Practical), and an N-Gain Score of 0.82 (High/Effective). These findings demonstrate that the Discovery learning-based worksheets are valid, practical, and effective in enhancing students' analytical skills at the C4 level of the Revised Bloom's Taxonomy, encompassing the sub-skills of differentiating, organizing, and attributing. The systematic integration of the six stages of Discovery learning into the worksheet activities guides students to develop their analytical skills in studying the material on infak and sadaqah.